Pengaruh Komposisi Foto De Tjolomadoe Melalui Instagram @detjolomadoe_official - Hanifa Izzati; Harry Kurniawan (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2023)
The De Tjolomadoe Museum was originally a sugar factory which later underwent a revitalization after being neglected for 20 years by carrying out the concept of adaptive reuse. After the revitalization was completed, the building was reopened as a museum along with various other supporting functions. The widespread use of social media such as Instagram among the public, the De Tjolomadoe Museum also uses Instagram as a medium to interact and attract the attention of the wider community to visit this museum. As a result, many people are interested in visiting and documenting it through photos which are then uploaded to social media and uploaded by tagging the official Instagram account @detjolomadoe_official. This study aims to find the effect of photo composition on the architecture of the De Tjolomadoe Museum by uploading the Instagram photo tag @detjolomadoe_official. This research focuses on the exterior of the museum through photos tagged on the Instagram account @detjolomadoe_official. Photos are taken via screenshots which are then processed by classifying them based on the composition used. The research is continued with analysis and discussion in accordance with related theories. The discussion starts with photo composition preferences, layers in photos, and building elements that appear in photos. The photos obtained were able to strengthen the character of the De Tjolomadoe Museum into a monumental building because of its compositional arrangement.